Changing in organic carbon dynamics and biological activities in clay loam brown forest soil by application of municipal sewage sludge - Bayoumi Hamuda , Hosam E. A. F. (TÁJÖKOLÓGIAI LAPOK, 2014)
A greenhouse pot experiment was conducted to assess the effects of two municipal sewage sludges (MSS) application on change in the dynamics of organic carbon, microbial population, enzymatic activities and alfalfa growth in relation to heavy metal content and nutrient release from sewage sludge in clay loam brown forest soil. The treatment of MSS increases soil organic matter and improves soil structure. Municipal sewage sludge of high heavy metal content (HHM) significantly decreased soil bioproductivity, reduced its biochemical properties, and lowered the microbial contents in comparison with MSS of low heavy metal (LHM) content. Total alfalfa dry matter yield and nitrogen content increases linearly with increasing MSS application rates. Soil treated with MSS rates of 40 and 60 % exhibit higher in crop dry matter, microbial contents and enzymatic activities than the control. Overall, our results demonstrate that soil treated with LHM content can improve soil quality and soil biological and biochemical properties.